CAN WE DEVELOP OUR DAILY VOCABULARIES BY FOLLOWING NATIVE ENGLISH SPEAKERS ON TWITTER? - Adinova, Deka; Christianti, Merry; Sayekti, Nurul; Amanda, Stella (Prosiding PESAT, 2013)
Twitter as a microblogging site is used by many people in the world for many functions. One of them, we can see people making conversation in their own language and “following” native English speakers (L1). The problem is: can follow L1 help us improve our English skill? The aim of this research is to know whether following L1 on Twitter can improve English daily vocabularies or not. We use qualitative research method to collect data. By dividing people into three groups: (1) people who are following mostly L1, (2) people who are following few L1 and (3) people who are not following L1 at all. We ask some questions related to English daily vocabularies which are some of the most often used in conversation. To conduct this research, we also use Tweepi.com to prove that the participants are truly following L1. In this end of research, we are going to know whether following L1 give Twitter users improvement in English daily vocabularies or not.